Adaptive Beamforming and Ai-Driven Low-Power Signal Processing on ‎Fpga For 6G Networks (Journal of University of Babylon for Engineering Sciences, 2025)
As the demands of sixth-generation (6G) networks escalate towards achieving high speeds and improved energy efficiency, there is an increasing need for intelligent and real-time adaptive solutions within the physical processing layer. This study proposes an innovative engineering framework based on an encapsulated architecture utilising FBGA (micro-distributed spherical array) technology, integrated with an internal artificial intelligence module, to achieve adaptive beamforming with high efficiency in dense wireless environments. The primary objective of this research is to develop an intelligent communication architecture that determines the optimal transmission angles and regulates power consumption in real-time by integrating artificial intelligence algorithms with hardware acceleration.The main contribution is to develop a practical model that combines mathematical precision with physical implementation, utilising an FBGA-based helicopter design and supported by comprehensive simulation within the MATLAB/Simulink environment. The experimental results demonstrated a significant improvement in performance indicators, including a 42% reduction in response time, a 35% decrease in power consumption, and an average signal quality improvement of 3.8 dB. These results highlight the effectiveness of the proposed design as a promising solution for building intelligent, high-performance, and low-consumption 6G communication networks.